Pendampingan Penyusunan Lembar Kerja Peserta Didik Berbasis Aplikasi Android Pada Mata Pelajaran Matematika - Indrie Noor Aini; Kiki Nia Sania Effendi; Odang Kusmayadi (Jurnal Pengabdian Pada Masyarakat, 2022)
The problems encountered by partners are as follows: (a) The use of learning materials hasn't adapted to the needs of students; (b) Lack of ability and willingness of teachers in preparing LKPD; (c) Lack of teacher ability in understanding android applications; (d) Demands during the pandemic that demands online learning. Furthermore, The stages of this activity go through three stages, namely preparation, core, and evaluation. The purpose of this research is to offer the following solutions: (a) Preparation of LKPD tailored to the needs of students, the output is a draft LKPD; (b) Provide direction and assistance to teachers to be able to compile their LKPD, the output is LKPD which is ready to be entered into the android application; (c) Provide direction and assistance to teachers to understand android applications, as evidenced by a questionnaire given to determine the level of teacher knowledge of mentoring materials; (d) Develop LKPD based on android applications that can use in everyday mathematics learning, the output is an android application that is given a name by each mentoring participant in this case the Mathematics Subject Teacher contains the LKPD he developed. The result of implementing this activity is the increasing interest of the training participants in making android-based LKPD. So that this activity can solve the problem well.